The Morphosyntactic level in Functional Discourse Grammar “A Practical Study in Arabic and English” - Turki Atiyah, Anwar (International Journal of Psychosocial Rehabilitation, 2019)
This study discusses how the morphosyntactic level in English language is different from that of Arabic language. This difference will be manipulated in the grammatical theory framework, Practical Converse Grammar. This theory explains how linguistic utterances are shaped, according to the outcomes and knowledge of native speech users. In doing so, it disparities with grammar of Chomskyan transformational. The upper -level unit of dissection in practical converse grammar is the „converse move‟, not the sentence prison purview or the clause. Therefore, practical converse grammar apart from numerous other linguistic views, containing its grandparent‟s functional grammar theory. Also this paper will show that FDG offers a framework within which known processes of grammaticalization can be captured. Contentive change is predicted, following FDG‟s hierarchical organization, to be restricted to those processes that lead to scope increase both within and across levels. Formal changes can be captured in a cross linguistically valid way by adopting Keizer‟s grammaticalization scale rather than traditional ones. Finally, congestive and formal scales can be linked in a typologically adequate way by assuming a relative rather than absolute relationship between them.